MOLECULAR DETECTION AND CLONING FOR RICKETTSIA-LIKE BACTERIA OF MILKY HAEMOLYMPH DISEASE OF SPINY LOBSTER Panulirus spp. - Isti Koesharyani; Lila Gardenia; Ni Luh Anggra Lasmika (Indonesian Aquaculture Journal, 2016)
Spiny lobster (Panulirus homarus and Panulirus ornatus) are important commodities for Indonesia. The aquaculture of lobster is susceptible for several diseases like parasite, fungi, bacteria, and virus. Among those diseases, milky haemolymph disease (MHD) is often seen as a symptom to mass mortality occurred at lobster farms in Gerupuk Bay of Lombok. The purpose of this study was to determine the lobster diseases on cage culture in Gerupuk Bay of Lombok, West Nusa Tenggara. The study was undertaken from January to March 2015. Diseases status was determined by application of molecular plat-form, polymerase chain reaction (PCR) with designation of specific primer for MHD (254F/R), 254F: 5’-CGA-GGA-CCA-GAG-ATG-GAC-CTT-3’ and 254R: 5’-GCT-CAT-TGT-CAC-CGC-CAT-TGT-3’ with PCR size product of 254 bp. and for cloned the pathogen was used TA-cloning Invitrogen for the DNA plasmid as positive control for other analysis. Several tissue samples i.e hepatopancreas, haemolymph, part of muscle hepatopancreas P. homarus and P. ornatus were taken from cage culture farms at Gerupuk Bay then preserved on 90% ethanol for further analysis by PCR and then the amplificated DNA were cloned into pCR®2.1 plasmid and transformed into competent E. coli. The result showed that almost all lobster samples from Gerupuk Bay were positive infected by MHD, as the results of PCR amplification whereas the band appeared at 254bp. Also MHD plasmid has been successfully cloned and will be used for further examination. Histopathologically in hepatopancreas infection have seen necrosis that contain numerous of rickettsia-like bacteria.